Highschool Students’ Professional Values Profiles - Laurentiu G. Tiru (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2020)
The main purpose of this study is to determine the work values of high school students and to compare the differences between students from different residence places (developed and underdeveloped cites). We used a quantitative approach in order to determine the influence of the variable mentioned above on the attitudes and beliefs regarding work values. To collect data, we used The Multidimensionality Work Ethic Profile, an inventory that measures seven dimensions of work values: self-reliance, morality, leisure, hard work, the centrality of work, wasted time, and delay of gratification. The research tool was applied to a sample of 214 high school students coming from two different residence environments characterized by different levels of development. We performed a series of Independent T tests in order to compare the scores that were given to each dimension. We discovered that the students, regardless of their residence environment, place the same value on the seven dimensions.